Electrophysiological evidence of atypical visual change detection in adults with autism - Clery, Helen; Roux, Sylvie; Houy-Durand, Emmanuelle; Bonnet-Brilhault, Frédérique; Bruneau, Nicole; Gomot, Marie (Frontiers in Human Neuroscience, 2013)
Although atypical change detection processes have been highlighted in the auditory modality in Autism Spectrum Disorder (ASD), little is known about these processes in the visual modality. The aim of the present study was therefore to investigate visual change detection in adults with ASD, taking into account the salience of change , in order to determine whether this ability is affected in this disorder. Thirteen adults with ASD and 13 controls were presented with a passive visual three stimuli oddball paradigm. The findings revealed atypical visual change processing in ASD. Whereas controls displayed a vMMN in response to deviant and a novelty P3 in response to novel stimuli, patients with ASD displayed a novelty P3 in response to both deviant and novel stimuli. These results thus suggested atypical orientation of attention towards unattended minor changes in ASD that might contribute to the intolerance of change.